Escherichia coli Sequence Type 457 Is an Emerging Extended-Spectrum-β-Lactam-Resistant Lineage with Reservoirs in Wildlife and Food-Producing Animals - Nesporova, Kristina; Wyrsch, Ethan R; Valcek, Adam; Bitar, Ibrahim; Chaw, Khin; Harris, Patrick; Hrabak, Jaroslav; Literak, Ivan; Djordjevic, Steven P; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2020)
Silver gulls carry phylogenetically diverse Escherichia coli, including globally dominant extraintestinal pathogenic E. coli (ExPEC) sequence types and pandemic ExPEC-ST131 clades; however, our large-scale study (504 samples) on silver gulls nesting off the coast of New South Wales identified E. coli ST457 as the most prevalent. A phylogenetic analysis of whole-genome sequences (WGS) of 138 ST457 samples comprising 42 from gulls, 2 from humans (Australia), and 14 from poultry farmed in Paraguay were compared with 80 WGS deposited in public databases from diverse sources and countries. E. coli ST457 strains are phylogenetic group F, carry fimH145, and partition into five main clades in accordance to predominant flagella H-antigen carriage. Although we identified considerable phylogenetic diversity among the 138 ST457 strains, closely related subclades (<100 SNPs) suggested zoonotic or zooanthroponosis transmission between humans, wild birds, and food-producing animals. Australian human clinical and gull strains in two of the clades were closely related (≤80 SNPs). Regarding plasmid content, country, or country/source, specific connections were observed, including I1/ST23, I1/ST314, and I1/ST315 disseminating blaCMY-2 in Australia, I1/ST113 carrying blaCTX-M-8 and mcr-5 in Paraguayan poultry, and F2:A-:B1 plasmids of Dutch origin being detected across multiple ST457 clades. We identified a high prevalence of nearly identical I1/ST23 plasmids carrying blaCMY-2 among Australian gull and clinical human strains. In summary, ST457 is a broad host range, geographically diverse E. coli lineage that can cause human extraintestinal disease, including urinary tract infection, and displays a remarkable ability to capture mobile elements that carry and transmit genes encoding resistance to critically important antibiotics.
Keywords: Animals; Escherichia coli Infections; infekce vyvolané Escherichia coli; Escherichia coli; beta-laktamasy; Australia; divoká zvířata; lidé; Anti-Bacterial Agents; beta-Lactamases; Austrálie; Phylogeny; beta-laktamy; plazmidy; Animals, Wild; beta-Lactams; Plasmids; zvířata; antibakteriální látky; fylogeneze; Humans